O MARKETING SOCIAL E A PROMOÇÃO DE MUDANÇAS ESTRUTURAIS NO ALEITAMENTO MATERNO - OLIVA MARIA DOURADO MARTINS; ARMINDA MARIA FINISTERRA DO PAÇO; EMERSON WAGNER MAINARDES; RICARDO GOUVEIA RODRIGUES (RAE: Revista de Administração de Empresas, 2014)
To assess the practical implications in relation to the breastfeeding behavior, regarding the dimension of the structural problems in the framework of social marketing, a qualitative exploratory research based on the Social Ecological Model (SEM) was developed, through in-depth interviews with lactation counselors and consultants in Portugal. The content of these interviews revealed some of the key barriers to breastfeeding behavior in the dimension of the structural problems and in the context of social marketing.